Photocatalysis vs. anodic-breakdown catalysis on TiO 2 layers - Paramasivam, Indhumati; Singh, S.; Moll, Matthias; Hauser, Christina; Meyer, Karsten; Schmuki, Patrik (Electrochimica Acta, 2012)
The present work compares two degradation approaches for organics molecules on TiO by (i) classical photocatalysis and (ii) anodic-breakdown (AB) catalysis. For this, TiO layers prepared by electrochemical anodization and annealing were used for the decomposition of crystal violet. AB-catalysis was performed at various applied potentials and the degradation kinetics and products were analysed. From the present results one can deduce that a valence band hole ejection mechanism is operative for AB catalysis and photocatalysis. We explain AB catalysis in terms of a Fowler-Nordheim type of junction breakdown model. © 2012 Elsevier Ltd. All rights reserved.